2008
DOI: 10.1080/02841850802512449
|View full text |Cite
|
Sign up to set email alerts
|

Proton magnetic resonance spectroscopic findings of cerebral fat embolism induced by triolein emulsion in cats

Abstract: Cerebral fat embolism induced by a triolein emulsion resulted in no significant change in the major metabolites of the brain in the acute stage, except for an elevated lipid/Cr ratio, which suggests the absence of any significant hypoxic-ischemic changes in the lesions embolized using a fat emulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Thus, the dosage of triolein emulsion required to increase vascular permeability while minimizing interstitial edema should be optimized. In previous studies, the amount of triolein emulsion (0.05-0.2 mL triolein in 20 mL saline) administered have varied widely (6-8), and dosages were not optimized. Kim et al (9) reported that the proper dosage of triolein emulsion required to increase vascular permeability with minimal edema appears to be approximately 3 mL/kg of triolein in a cat model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dosage of triolein emulsion required to increase vascular permeability while minimizing interstitial edema should be optimized. In previous studies, the amount of triolein emulsion (0.05-0.2 mL triolein in 20 mL saline) administered have varied widely (6-8), and dosages were not optimized. Kim et al (9) reported that the proper dosage of triolein emulsion required to increase vascular permeability with minimal edema appears to be approximately 3 mL/kg of triolein in a cat model.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the development of cerebral fat embolisms depends on the morphology of the embolized fat and the size of the fat particles. The increased vasogenic edema induced by triolein emulsion is reversible and does not cause any significant histological changes, hemodynamic occlusive appearance, or metabolic differences in the brain (Kim et al., 2004 , 2006 ; Baik et al., 2008 ).…”
Section: Discussionmentioning
confidence: 99%